HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PARTISIPASI MASYARAKAT DALAM MELAKSANAKAN VAKSINASI COVID-19 DI DESA CINTANAGARA KECAMATAN CIGEDUG KABUPATEN GARUT - Siti Saadah; Sri Maywati; Neni Neni (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2023)
The World Health Organization (WHO) in China reported a case of pneumonia of unknown etiology in Wuhan, Hubei Province, China. On January 7, 2020, China identified the case as a new type of coronavirus. Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. The village that had the lowest percentage of COVID-19 vaccination achieved in the working area of the Sukahurip Health Center was Cintanagara Village with the percentage of first dose of COVID-19 vaccination achieved 66.95%, second dose 24.46%, and third dose 0.90%. The purpose of this study was to determine the relationship between knowledge and attitudes with community participation in carrying out the COVID-19 vaccination in Cintanagara Village, Cigedug District, Garut Regency. This research method is a quantitative type with a cross sectional approach involving 363 respondents with a chi square test analysis. The results showed that there was a relationship between knowledge and community participation in carrying out the COVID-19 vaccination (p-value=0.0440.05) and there was no relationship between attitudes and community participation in carrying out the COVID-19 vaccination (p-value=0.3950.05). Suggestions for respondents are that they can understand well information related to COVID-19 vaccination, and actively seek information about COVID-19 vaccination in the mass media or other sources. This information is expected to increase respondents' knowledge about COVID-19 vaccination.